Data-constrained Magnetohydrodynamic Simulation for Magnetic Flux Rope Eruptions Driven by Magnetic Reconnection - Liu, Nian; Inoue, Satoshi; Wang, Ying; Wang, Haimin (The Astrophysical journal, 2025)
We conducted data-constrained magnetohydrodynamic (MHD) simulations for solar active region (AR) NOAA AR 11429, which produced two X-class flares within a span of 63 minutes. The simulations were performed using the zero- β MHD approximation, with the initial condition derived from the nonlinear force-free field extrapolated from the photospheric magnetograms taken 2 hr before the first X5.4 flare. During the simulation, we enhanced magnetic reconnection locally by applying anomalous resistivity in the induction equation within the regions of interest. As a result, the simulations successfully reproduced the expansion of two magnetic flux ropes (MFRs) corresponding to the two observed eruptions. The result shows that the difference in stability between the two MFRs is related to the location of the magnetic reconnection that triggers the solar eruptions. Furthermore, comparison with the analysis of failed MFR eruptions indicates that both the initiation reconnection and the subsequent driving mechanism, torus instability, are equally important for a successful eruption. This simulation reveals a new mechanism in which long loops, formed via tether-cutting reconnection, push up the overlying twisted field lines, leading to their destabilization by torus instability.